Do the saving interest in Islamic banks affected by financial literacy and religiosity? - Ayu Nursari; Apriani Dorkas Rambu Atahau; Imanuel Madea Sakti (Jurnal Penelitian, 2022)
This study examines the effect of financial literacy and religiosity on interest in saving at Islamic banks in the people of Tlogomulyo District, Temanggung Regency. This study uses a quantitative approach with the data used using primary data using an online questionnaire via a google form. The questionnaire was taken using the purposive sampling technique with the number of samples used in this study being 76 respondents. This research was conducted using the multiple regression analysis methods and tested using SPSS. The test results prove that religiosity has a positive effect on interest in saving in Islamic banks in the people of Tlogomulyo District, Temanggung Regency. While financial literacy does not affect the interest in saving in Islamic banks in the people of Tlogomulyo District, Temanggung Regency.